Intestinal microbiota composition and peripheral blood Th cell subsets in patients with multiple sclerosis - I. N. Abdurasulova; E. A. Tarasova; I. V. Kudryavtsev; I. G. Negoreeva; A. G. Ilves; M. K. Serebriakova; E. I. Ermolenko; E. V. Ivashkova; A. V. Matsulevich; A. E. Tatarinov; I. D. Stoliarov; V. M. Klimenko; et al. (Инфекция и иммунитет, 2019)
At present, the role of intestinal microbiota in diverse diseases of the central nervous system, including of multiple sclerosis (MS) has been extensively investigated. Self-reactive CD4+ Th1 and Th17 cells specific to myelin-derived antigens play a key role in the MS pathogenesis. Taking into consideration pathogenetic features related to MS development, we examined a relation between intestinal microbiocenosis and abundance of various peripheral blood helper T (Th) cell subsets in MS patients. Objective of the study: to assess prevalence of individual members of the intestinal microbiota in MS patients and analyze a relation with peripheral blood Th cell subsets. Prevalence of symbiotic and opportunistic microbial species was estimated by bacteriological method and real time PCR in 112 MS patients (72 females, 40 males) of varying severity and duration. Th cell subsets (Th1, Th2, Th17, Th1/Th17, Th17/Th22, DP Th17) were analyzed by using multi-color flow cytometry based on Th cell subset-specific surface expression of chemokine receptors. A relationship between individual intestinal microbiota species and severity, duration and rate of MS progression, as well as with the phenotype of immune cells was assessed. It was found that the most significant correlation between percentage of peripheral blood Th cell subsets was observed with prevalence of Lactobacillus spp., Enterococcus spp. and Enterobacter spp. Moreover, prevalence of Enterococcus spp. Th cell composition influenced synergistically or antagonistically together with Enterobacter spp. or Lactobacillus spp., respectively. It is suggested that direct and indirect impact of intestinal microbiota composition on human immune system might contribute to developing novel strategies for treating MS.